Leucocytosis in Febrile Seizure - Ojha, AR; Aryal, UR (Journal of Nepal Paediatric Society, 2011)
Introduction: Febrile seizure (FS) is a common condition affecting 2-5% of children. Peripheral blood leucocyte count with its differential is an initial test looking for the cause of fever and high count is usually accounted for the seizure activity. Objectives: To find the incidence of febrile seizure and to evaluate the relationship between fever duration before seizure, seizure duration and the total leucocyte as well as neutrophil response. Methodology: It is a cross sectional study done at Kathmandu Medical College and Teaching Hospital, Kathmandu, Nepal, for one year. After an informed consent, children from 6 months to 6 years with FS were admitted. Those with afebrile seizures and who refused to give consent were excluded. A detail history and examination was done on admission. All were investigated for the source of fever including total and differential count. Results: Out of a total 1742 children admitted, 115 (6.6%) children had febrile seizure. Simple febrile seizure was observed in 93(81%) and 22(19%) was complex febrile seizure. 42% of them had leucocytosis. The duration of fever before the onset of seizure is found to be negatively correlated with total leucocyte count (r = -0.418, p<0.001) and neutrophils count alone (r = -0.375, p<0.001). The duration of seizure is not correlated to both the total leucocyte count (r = -0.162, p = 0.85) and the neutrophil (r = -0.109, p= 0.247). Conclusion: The incidence of febrile seizure is 6.6%. Leucocytosis and neutrophilia in children is negatively correlated with the duration fever before the onset of seizure, associated with underlying infection if any and is not related to seizure event and its duration. Thus any child with febrile seizure with high leucocyte count should be evaluated for infection. Key words: Fever; Leucocytosis; Neutrophilia; Seizure DOI: http://dx.doi.org/10.3126/jnps.v31i3.4577 J Nep Paedtr Soc 2011;31(3):188-191